2023
DOI: 10.21203/rs.3.rs-3158251/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biosynthesis of apigenin glucosides in engineered Corynebacterium glutamicum

Abstract: Background; Glucosylation is a well-known approach to improve the solubility, pharmacological and biological properties of flavonoids. In recent years, efforts such as enzymatic synthesis have been developed to enhance the production of flavonoid glucosides. However, the low yield of products coupled with the requirement of expensive UDP-sugars limits the application of these systems for large-scale synthesis for human needs. C. glutamicum is a Gram-positive and generally regarded as safe (GRAS) bacteria freq… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…In Yarrowia lipolytica this challenge of complexity was tackled by the establishment of an alternative plant-derived astaxanthin biosynthesis from Adonis aestivalis 20 resulting in astaxanthin as the exclusive hydroxylated carotenoid due to the sequential activity of carotenoid 4-hydroxy-β-ring 4-dehydrogenase (HBFD) and carotenoid β-ring 4-dehydrogenase (CBFD). It was recently demonstrated that also the UDP-glucose pool can be enhanced by overexpression of the endogenous UDPd-glucose pathway genes, phosphoglucomutase (pgm) and UDP-d-glucose pyrophosphorylase (galU1) together with the heterologous expression of ydhE from Bacillus licheniformis 65 and this strategy might also improve the biosynthesis of glycosylated carotenoids.…”
Section: Discussionmentioning
confidence: 99%
“…In Yarrowia lipolytica this challenge of complexity was tackled by the establishment of an alternative plant-derived astaxanthin biosynthesis from Adonis aestivalis 20 resulting in astaxanthin as the exclusive hydroxylated carotenoid due to the sequential activity of carotenoid 4-hydroxy-β-ring 4-dehydrogenase (HBFD) and carotenoid β-ring 4-dehydrogenase (CBFD). It was recently demonstrated that also the UDP-glucose pool can be enhanced by overexpression of the endogenous UDPd-glucose pathway genes, phosphoglucomutase (pgm) and UDP-d-glucose pyrophosphorylase (galU1) together with the heterologous expression of ydhE from Bacillus licheniformis 65 and this strategy might also improve the biosynthesis of glycosylated carotenoids.…”
Section: Discussionmentioning
confidence: 99%
“…Although various types of diversified flavonoids have been synthesized in E. coli and S. cerevisiae, glycosylation of flavonoids has been reported as only modification of flavonoid in engineered C. glutamicum [57,58]. Glycosylation is catalyzed by glycosyltransferase, which transfers sugar molecules into the oxygen, carbon, nitrogen, and sulfur atoms of aglycon.…”
Section: Improving Intracellular Udp-sugar Level For Biosynthesis Of ...mentioning
confidence: 99%